The process of second language acquisition (Eurasian Journal of Philology Science and Education, 2015)
The article refers to the process of second language acquisition, that is, about the formation and development of bilingualism. Emphasizes the idea that the knowledge of a new language via the native language and, therefore, a conceptual picture of the target language "grows" from a conceptual picture of the mother tongue. The material in this article was a professional focus in teaching a second language. Also, the authors suggest that bilingual development of the subject is when he begins to consciously compare the target language with a native, to build their statements on the basis of the nature of the other language, and not by analogy with the family. As a result of learning a second language education is in the minds of bilingual learning structure that accommodates two language systems , one of which later , and so it is " embedded " in the already formed an earlier system of the native language . The authors attempted to examine in detail the process of formation and development of bilingualism, noting its several components of the process of becoming. In today's world, when there is a policy of globalization, language becomes a pressing need. Some high schools have moved to Kazakhstan bilingual education when teaching profession is in a foreign language. This article is not universal, and will help teachers understand the process offormation of bilingualism and to help develop its methodology for language teaching.
Keywords: bilingualism; bilingual structure; internalization; the mechanism of recoding